THE MAGNESIUM ABUNDANCE IN THE THIN AND THICK DISK OF THE GALAXY - Nykytyuk, T. V.; Mishenina, T. V. (Одеські астрономічні публікації, 2017)
The chemical evolution of the thin and thick disk of our Galaxy was investigated in framework of the opened model with gas inflow. It was supposed that the thin and thick disks separate chemically and spatially and have different evolution timescales. The Galactic evolution of magnesium was investigated for the thin and thick disk. The obtained results allow us that the star formation history of the thin disk is more smooth and quiet than its for the thick disk of our Galaxy.A gas infall plays an important role in an appearance of chemical distinctions of relative abundances between the thin and thick disk - a inflow rate is more intensive for the thick disk.